Firm dynamics and productivity growth - John Haltiwanger (EIB Papers, 2011)
Countries differ substantially in the extent to which more productive firms are large and/or are becoming larger and less productive firms are small and/or becoming smaller. A challenge for both emerging and advanced economies is that achieving such static and dynamic allocative efficiency requires an ongoing process of restructuring and reallocation. Such restructuring and reallocation is by its very nature costly. Market structure and institutions that promote well-functioning business dynamism are, accordingly, critical for economic performance. In the 1980s and 1990s, the US exhibited a robust pace of business dynamism that contributed substantially to US productivity and job growth. There are, however, some disturbing trends in the nature of US business dynamism - for example, the pace of business startups has declined secularly especially over the last decade. The decline in the pace of business dynamism may be contributing to the anaemic US recovery from the recent recession.
Keywords: 330; Unternehmenswachstum; Allokationseffizienz; Unternehmenssanierung; Produktivität; Wirtschaftswachstum; Schwellenländer; Industriestaaten; USA